Pediatric patients with inflammatory bowel disease exhibit increased serum levels of proinflammatory cytokines and chemokines, but decreased circulating levels of macrophage inhibitory protein-1β, interleukin-2 and interleukin-17. - Kleiner, Giulio; Zanin, Valentina; Monasta, Lorenzo; Crovella, Sergio; Caruso, Lorenzo; Milani, Daniela; Marcuzzi, Annalisa (Exp Ther Med, 2015)
Inflammatory bowel disease (IBD) is a chronic and progressive inflammatory condition of the gastrointestinal tract. Although the causative events that lead to the onset of IBD are yet to be fully elucidated, deregulation of immune and inflammatory mechanisms are hypothesized to significantly contribute to this disorder. Since the onset of IBD is often during infancy, in the present study, the serum values of a large panel of cytokines and chemokines in pediatric patients (<18 years; n=26) were compared with age-matched controls (n=37). While elevations in the serum level of several proinflammatory and immune regulating cytokines were confirmed, such as interleukin (IL)-1β, IL-5, IL-7, interferon (IFN)-γ-inducible protein-10, IL-16, cutaneous T-cell-attracting chemokine, leukemia inhibitory factor, monokine induced by γ-IFN, IFN-α2 and IFN-γ, notably decreased levels of IL-2, IL-17 and macrophage inhibitory protein-1β were also observed. Therefore, while a number of proinflammatory cytokines exhibit increased levels in IBD patients, pediatric IBD patients may also exhibit certain aspects of a reduced immunological response.